Microplastics and freshwater microalgae: what do we know so far? - Rani-Borges, Bárbara [UNESP]; Moschini-Carlos, Viviane [UNESP]; Pompêo, Marcelo (Springer Nature, 2021)
The constant entry of microplastics in several environmental matrices has been of great concern to the scientific community and to society in general, mainly due to the mysteries that surround the implications of this pollutant in the environment. Freshwater ecosystems are resources especially susceptible to variations in environmental quality, and the lack of data on the impacts caused by plastic fragments exacerbates the vulnerability of this environment. Considering the results of other studies, which demonstrate the increasing entry of polymeric fragments in the aquatic environment can lead to algae growth inhibition, an investigation was carried out to determine the current state of research on the interaction between microplastics and freshwater microalgae. In total, 20 scientific articles were analyzed. Different species were subjected to toxicological tests under controlled conditions in the laboratory with small microplastics (size range between 0.1 and 1000 µm), primary and secondary microplastics of different types of polymer. Four toxicity class of indicators were chosen to assess the microalgae response to exposure to microplastic in the selected studies: growth inhibition; photosynthetic activity; pigment analysis; and enzymatic activity and oxidative stress. In this review, a critical analysis is made on the effects of the shape, size, concentration, and duration of exposure to microplastics and research gaps are identified to guide future research priorities in this area of study.
Keywords: Chlorophyll a; Growth inhibition; Microalgae; Microplastic; Photosynthesis; Phytoplankton